2013
DOI: 10.1088/0957-4484/24/50/505720
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally fast water desalination at complete salt rejection by pristine graphyne monolayers

Abstract: Desalination that produces clean freshwater from seawater holds the promise of solving the global water shortage for drinking, agriculture and industry. However, conventional desalination technologies such as reverse osmosis and thermal distillation involve large amounts of energy consumption, and the semipermeable membranes widely used in reverse osmosis face the challenge to provide a high throughput at high salt rejection. Here we find by comprehensive molecular dynamics simulations and first principles mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 49 publications
(107 reference statements)
5
113
0
Order By: Relevance
“…By MD simulations and first principles modeling (Figure 5), it was found that pristine graphyne can achieve 100% rejection of ions in sea water, including Na + , Cl − , Mg 2+ , K + , and Ca 2+ , at an exceptionally high water permeability, about two orders of magnitude higher than that of commercial state-of-the-art reverse osmosis membranes with a salt rejection of 98.5% 68. This complete ion rejection by graphyne, independent of the salt concentration and the operating pressure, is revealed to originate from the significantly higher energy barriers for ions than for water 68. This intrinsic specialty of graphyne provides a new possibility for the efforts to alleviate the global shortage of fresh water and other related environmental problems.…”
Section: Graphynementioning
confidence: 99%
See 1 more Smart Citation
“…By MD simulations and first principles modeling (Figure 5), it was found that pristine graphyne can achieve 100% rejection of ions in sea water, including Na + , Cl − , Mg 2+ , K + , and Ca 2+ , at an exceptionally high water permeability, about two orders of magnitude higher than that of commercial state-of-the-art reverse osmosis membranes with a salt rejection of 98.5% 68. This complete ion rejection by graphyne, independent of the salt concentration and the operating pressure, is revealed to originate from the significantly higher energy barriers for ions than for water 68. This intrinsic specialty of graphyne provides a new possibility for the efforts to alleviate the global shortage of fresh water and other related environmental problems.…”
Section: Graphynementioning
confidence: 99%
“…It is worth noting that opposed to graphyne, graphdiyne is impermeable to water and ions due to its limited pore size 68. As a result, graphdiyne is not good for desalinators.…”
Section: Graphdiynementioning
confidence: 99%
“…[18] According to our calculations, α-, β-and γ-silagraphyne have the inverse of the specific surface area of 0.362, 0.432 and 0.537 mg/m 2 , respectively. This size of the pore is very important in the desalination of sea water, [19] photocatalyst, lithium-ion battery and energy storage, [4] because they have high porosity and high specific surface area compared to graphyne (i.e., 0.379 mg/m 2 for α-graphyne, 0.461 mg/m 2 for β-graphyne and 0.582 mg/m 2 for γ-graphyne). [18] The calculative ELF maps of silagraphyne monolayers are demonstrated in Fig S5. It's clear to see that all of the ELFs of C-C and Si-C bonds are localized at the bond center, similar to the ELF maps in t-SiC monolayer.…”
mentioning
confidence: 99%
“…GNC structures containing square and heptagonal motifs, i.e., GNC 11,15,and 18, are more rigid and exhibit highly localized flexibility at a median distance with the structure-specific motifs. In addition, these structures are characterized by a faster diffusion of water in the nanopores compared with the other GNC structures.…”
Section: ■ Conclusionmentioning
confidence: 99%